Sustainability Indicators Favor the Creation of Companies? - Piekas, Andrezza Aparecida Saraiva; Carvalho, Carlos Eduardo; Machado, Hilka Pelizza Vier; Teixeira, Eduardo Kunzel (REGEPE Entrepreneurship and Small Business Journal, 2020)
Objective: To analyze the relationship between sustainability indicators and the creation of companies. Method: This study is characterized as quantitative and explanatory. Both relationship modeling and hypothesis testing were performed by regression analysis from secondary data. Two models were tested using five variables. Secondary data regarding Sustainability indicators were collected from the Santa Catarina Federation of Municipalities (FECAM) databases, from the Sustainable Municipal Development Indicators System (SIDEMS). Data regarding the creation of companies in each municipality were obtained from the Federation of Industries of the State of Santa Catarina (FIESC). Originality / Relevance: This study provides evidence that, besides the influence of aspects associated with the national environment, the local environment, represented by the municipality, positively influences the creation of companies. Results: It was found that the Sustainable Municipal Development Index (IDMS) influenced the number of companies created in Santa Catarina municipalities. Percentage changes in the sustainable development index cause more than proportional percentage changes in the number of companies created. The dimensions that had the greatest impact on the relationship studied were sociocultural and environmental. Theoretical / Methodological Contributions - This research contributes to the fields of study in Entrepreneurship and Sustainability by demonstrating that municipalities with higher sustainability indicators tend to create more companies. This demonstrates the importance of municipal public policies aimed at sustainable development.